2019
DOI: 10.1038/s41598-019-49484-4
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment with the CDK4/6 inhibitor palbociclib improves the efficacy of paclitaxel in TNBC cells

Abstract: Triple Negative Breast Cancer (TNBC) is a challenging disease due to the lack of druggable targets; therefore, chemotherapy remains the standard of care and the identification of new targets is a high clinical priority. Alterations in the components of the cell cycle machinery have been frequently reported in cancer; given the success obtained with the CDK4/6 inhibitor palbocicib in ER-positive BC, we explored the potential of combining this drug with chemotherapy in Rb-positive TNBC cell models. The simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 39 publications
(53 reference statements)
3
60
0
Order By: Relevance
“…Paclitaxel has been shown to be useful in the chemotherapy of multiple cancers, including breast cancer, 26 it retards cell cycle progression and induces apoptosis to inhibit tumor cell growth. 27 In order to reveal the function of circ_0006528 in PTX-resistant breast cancer cells, loss-of-function assays were performed, and we found that its knockdown decreased the IC50 value of PTX as well as hindered cell proliferation, migration, invasion and autophagy, and induced cell apoptosis in breast cancer in vitro. Therefore, we hypothesized that circ_0006528 might exist in breast cancer as an oncogene, and its biological function might be related to PTX resistance.…”
Section: Discussionmentioning
confidence: 96%
“…Paclitaxel has been shown to be useful in the chemotherapy of multiple cancers, including breast cancer, 26 it retards cell cycle progression and induces apoptosis to inhibit tumor cell growth. 27 In order to reveal the function of circ_0006528 in PTX-resistant breast cancer cells, loss-of-function assays were performed, and we found that its knockdown decreased the IC50 value of PTX as well as hindered cell proliferation, migration, invasion and autophagy, and induced cell apoptosis in breast cancer in vitro. Therefore, we hypothesized that circ_0006528 might exist in breast cancer as an oncogene, and its biological function might be related to PTX resistance.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, palbociclib also seems to be able to inhibit GLUT1 mediated glucose uptake and metabolism in TNBC cells [87,88]. Moreover, combination of palbociclib with a chemotherapeutic agent currently used for the treatment of TNBC patients (paclitaxel) inhibited cell proliferation and increased cell death more efficiently than single treatments, associated with a more marked effect on glucose uptake and consumption and on GLUT1 protein levels [87]. Additionally, combination of palbociclib with a PI3K/mTOR inhibitor (BYL719) enhanced the antitumoral effect of these agents and the negative effect of each of these drugs on glucose uptake and consumption and on GLUT1 protein levels (Table 1) [88].…”
Section: Palbociclibmentioning
confidence: 98%
“…Palbociclib, an orally-available inhibitor of CDK4 and CDK6, represents the most widely studied compound among cell cycle inhibitors [86]. Interestingly, palbociclib also seems to be able to inhibit GLUT1 mediated glucose uptake and metabolism in TNBC cells [87,88]. Moreover, combination of palbociclib with a chemotherapeutic agent currently used for the treatment of TNBC patients (paclitaxel) inhibited cell proliferation and increased cell death more efficiently than single treatments, associated with a more marked effect on glucose uptake and consumption and on GLUT1 protein levels [87].…”
Section: Palbociclibmentioning
confidence: 99%
“…Paclitaxel inhibits palbociclib-mediated AKT induction and downregulates the RB/E2F/c-myc signaling pathway. The sequential combination of palbociclib/paclitaxel can enhance the inhibitory effects on glucose metabolism, and pretreatment with palbociclib can significantly improve the therapeutic effect of chemotherapy [172]. However, the simultaneous use of palbociclib and paclitaxel produces an antagonistic effect.…”
Section: The Combined Treatment With Cdk Inhibitors and Other Agentsmentioning
confidence: 99%